STUDI KELAYAKAN BISNIS ONLINE TRAVEL AGENT - Timothy Andrianus Philemon; Inge Barlian Sundjaja; Arip Budiono (Business Administration Department - Universitas Katolik Parahyangan, 2018)
Conventional travel agents have declining sales over the past few months. The decline is caused by the number of an online travel agent that has sprung up. Contrary to the decline in the sales of conventional travel agencies, online travel sales continue to increase to date. Although it is well known that the online travel business has the prospect of growing, but there are some things to consider before running a business.Before opening an online travel business, a business feasibility study needs to be done so that this new business can run well. Based on feasibility studies that have been done, it can be seen that the online travel business can be considered feasible. On the legal, technical, and management aspects, all needs can be met by the online travel business. There are emerging market opportunities in the market aspect and determined that its target market is the backpacker segment. In the financial aspect, the business is considered feasible in the optimistic and most likely scenario. In contrast, in the pessimistic scenario, it is not feasible because it does not meet the three criteria of assessment.